A Morphosyntactic Change in Progress: English Noun-Incorporating Compound Verbs - Tarpent, Marie-Lucie (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2001)
The first English-speaking describers of Amerindian languages were struck by a common morphological process which incorporated nouns, usually Direct Objects, into the verb. Little did they know that such a process would eventually become an integral part of English grammar. According to most textbooks, compounding in English is a process which creates nouns and adjectives, but not verbs. Cases such as to babysit are considered exceptional, and marginal since they are backformed from compound nouns such as babysitter. Such descriptions may have been correct two or three decades ago, but nowadays the use of compound verbs such as to fund raise, to revenue share, to guest conduct, backformed from nouns or adjectives, has become so common that it seems strange for linguists to continue to ignore it. Like any other productive linguistic process, backformation in this case follows specific steps and patterns, which in turn provide models for what appear to be new creations. This evolution currently in progress in English gives linguists a wonderful opportunity to observe the conditioning and the development of the noun-incorporating process, as well as to confirm the constant tension in the language between the two opposite tendencies of synthesis and analysis.